A prey predator model with disease in prey and recovery (Nonlinear Studies, 2020)
We consider a three dimensional system of the predator-prey mathematical model with disease in prey. This system has a prey predator model with disease is transmitted according to non-linear incidence rate and with ratio-dependent Michaelis-Menten (Holling-type-II) functional response. We have discussed the stability analysis of the system. We have also discussed that a Hopf-bifurcation mechanisms around the interior equilibrium point, taking rate of infection and recovery rate of infected prey are bifurcation parameters. The analytical nding are supported by numerical observations.